Environmental Impact Study A preventive mechanism for environmental protection in Algerian law - labassia Chettih, Imane (International Journal of Psychosocial Rehabilitation, 2022)
The study of environmental impact is among the most important preventive principles aimed at achieving proactive protection before harm is caused by a predictive study of developmental projects or activities with a negative environmental impact that affects human health and other natural organisms. It is based on scientific and technical bases that enable us to interpret and analyze these effects and to develop appropriate solutions to minimize or minimize their effects.